Financial literacy education and retirement planning of the urban elderly in Malaysia / Visyalini Selvadurai - Visyalini, Selvadurai (2018)
Financial literacy education and retirement planning has recently been highlighted as the contributing factor towards successful retirement planning. The purpose of this study is to identify the key determinants affecting financial retirement planning for the urban elderly in Malaysia. The main key determinants focused in this thesis were demographic, financial attitude, financial education and financial literacy factors. This research applied both quantitative and qualitative methodology. Data was collected through survey and interview. The first survey and second survey were done among 1239 and 623 elderly individuals respectively in the Klang Valley. Simple random sampling was used to select elderly individuals based on electoral roll. Interview was also conducted with ten elderly individuals in the Klang Valley. Purposeful sampling was used in the selection of elderly individuals for interview. Descriptive and inferential statistics were used to analyse the quantitative data. Thematic analysis was used to analyse the qualitative data. In the first cohort of survey, the findings of binary logistic regression analysis depicted that the level of education, owning luxury amenities and minimum monthly expenses were vital determinants of managing monthly expenditure for elderly individuals. Furthermore, in the second cohort of survey the Pearson’s chi-squared in the cross-tabulation showed that age, gender, ethnicity and education level were significant factors that determined financial retirement planning. The Cramer’s V values showed that there was a positive relationship between age and comfortable retirement and monitoring spending .There was a positive relationship between gender and asset ownership, comfortable retirement, duration savings to last, estimation retirement savings and financial planning ways. Moreover, there was a positive relationship between ethnicity and comfortable retirement, duration saving to last and monitoring spending. There was a positive relationship between education level and ownership of assets, comfortable retirement, duration savings to last, estimation retirement saving, financial planning ways and monitoring spending. Further analysis using multinomial logistic regression indicated that male, duration saving to last (11and above years), productive income, non-productive income, direct dependency, both dependency, neglect spending, figuring out financial planning ways through family, friends and counseling, age 64 below, very confident with retirement because they have enough money to live comfortably throughout their retirement years and very confident with retirement because of family support were the important factors which determine the financial retirement planning. The qualitative result also suggested that mastering financial literacy was essential in planning for retirement. The analysis of interviews also indicated that psychological aspects like individuals’ initiative in setting monetary goals, individuals’ exposure on managing financial matters and individuals’ level of financial awareness contribute towards successful financial retirement planning. The findings provided essential insights to policy makers and governments in both developing and developed countries on the crucial determinants of financial literacy education that need to be emphasised to ensure successful financial retirement planning. Importantly, this study has contributed to the development of financial retirement planning conceptual model of the urban elderly which aids elderly individuals in enhancing their financial literacy education and planning their retirement well.